“MANGAN ORA MANGAN, SING PENTING KUMPUL” (MAKAN TIDAK MAKAN YANG PENTING KUMPUL) TINJAUAN FILOSOFIS “AKU DAN LIYAN” DALAM GAGASAN TOGETHERNESS PARA FILSUF BARAT - Evan Tandywijaya (Universitas Hasanuddin, 2020)
Javanese people are known for their rich and profound wisdom in life. Like a water source that never stops flowing, Javanese people never run out of sources of wisdom. One of the policies of the Javanese community that has been around for a long time but remains actual until now is “mangan ora mangan sing penting kumpul”. Today, the rapid development of technology makes people more individualistic and ignores the importance of togetherness. This is the background and purpose of this writing, namely as a reminder of the value of togetherness and see the depth of meaning contained in the philosophy of “mangan ora mangan sing penting kumpul”. The writer wants to see this philosophy in terms of the relationship between Eastern and Western philosophy and present it using narrative methods. Previous studies show that philosophy of